FAKTOR PENENTU KEBERHASILAN PENGELOLAAN SATUAN PENDIDIKAN - Amran Amran (UNIVERSITAS BENGKULU, 2015)
This study aims to evaluate the determinants of successful management of educational units in SMP 6 Seluma. The method in this research is evaluative. Data collection techniques used in this study are: interviews, documentation, observation and questionnaires. The result of this research showed the critical success factors in the management of the school leadership, teachers, students, school committee. Suggestions research; need the commitment of the school manager to constantly improve the competence and leadership role and teachers to constantly renew its ability to be able to adjust to the changes that occur both within the work environment or in the surrounding environment.Keywords: determinants, success, management, education